If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (12x + 1) = (20x + 19) Reorder the terms: (1 + 12x) = (20x + 19) Remove parenthesis around (1 + 12x) 1 + 12x = (20x + 19) Reorder the terms: 1 + 12x = (19 + 20x) Remove parenthesis around (19 + 20x) 1 + 12x = 19 + 20x Solving 1 + 12x = 19 + 20x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-20x' to each side of the equation. 1 + 12x + -20x = 19 + 20x + -20x Combine like terms: 12x + -20x = -8x 1 + -8x = 19 + 20x + -20x Combine like terms: 20x + -20x = 0 1 + -8x = 19 + 0 1 + -8x = 19 Add '-1' to each side of the equation. 1 + -1 + -8x = 19 + -1 Combine like terms: 1 + -1 = 0 0 + -8x = 19 + -1 -8x = 19 + -1 Combine like terms: 19 + -1 = 18 -8x = 18 Divide each side by '-8'. x = -2.25 Simplifying x = -2.25
| 5(r-8)-4(6r-4)=-8r-8r | | 2x=5x+21-6 | | 3(1+11)= | | 5a^2+60a+180=0 | | 3x^2-18x-19=0 | | 2(1+x)=3(x+4) | | 9x+70=360 | | 2x(x-4)(x+8)=0 | | 3(5p-3)=5(p-1) | | 14x-3(2x-5)+2(5x-3)=6-5(2x-9) | | 3(y+30)=6y-4 | | 5(v-5)+3(v+2)=-4v+7+3v-2 | | 3(x+5)=5x+2.5 | | 117=6x-12+3x+3 | | (34-2)y=8 | | 8(5x-3)+4(1-8x)=3x-8+3x-2 | | 4u^2-2u=0 | | 10x5/2 | | 2p-10)/(8p-40) | | 6(9d)=3d | | 180=x+(0.05+x) | | (9x-2y)-(6x+2y)= | | 6(x-4)-4=8 | | 4logx-3logx=12 | | 238=16t^2+32t | | Xy=5x-2 | | x=13+0.75y | | 4lgx^3-3lgx^2=12 | | (5x-3)/3=4 | | 4logx^3-3logx^2=12 | | (-7)=g+(-5) | | 5a+1=8 |